2013
DOI: 10.3748/wjg.v19.i46.8709
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and distribution of colonic diverticulosis: Analysis of 2877 barium enemas in Thailand

Abstract: Colonic diverticulosis was identified in 28.5% of DCBE examinations in Thai adults. There was no association between the presence of diverticulosis and gender or age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 14 publications
1
18
1
5
Order By: Relevance
“…2 Importantly, this is in contrast to Asian series, where the incidence ranges from 22 to 50%. 1,3 When compared with sigmoid diverticulosis, cecal, or rightsided diverticulosis has several manifestations. In younger patients, it can occur in the form of a single, true diverticula near the ileocecal valve; in elderly patients, it can occur as a manifestation of pan-colonic diverticulosis or in association with a malignancy.…”
Section: Cecal Diverticula Overviewmentioning
confidence: 99%
“…2 Importantly, this is in contrast to Asian series, where the incidence ranges from 22 to 50%. 1,3 When compared with sigmoid diverticulosis, cecal, or rightsided diverticulosis has several manifestations. In younger patients, it can occur in the form of a single, true diverticula near the ileocecal valve; in elderly patients, it can occur as a manifestation of pan-colonic diverticulosis or in association with a malignancy.…”
Section: Cecal Diverticula Overviewmentioning
confidence: 99%
“…In Western countries, CRD is mainly located in the left-side colon, and multiple diverticula are more common [16,17]. In Asian countries, CRD is mainly located in the right-side colon, and single diverticulum is more frequent [18]. We found that, regardless of gender and age, CRD often involved a single segment, predominately seen in the right-side colon (77.0% for male and 74.1% for female) and the rarest in rectum.…”
Section: Discussionmentioning
confidence: 99%
“…Double-contrast barium enema is often appliedt oC Ti maging of the colon, and the gas administered orally can help to distend the bowel, which enhances the contrast and allows for betterdifferentiation of abnormal morphologyfrom normaltissues. [78] Barium is used to outline the colon and rectum,a nd air is pumped into the rectum and colon to enhance the imaging further by distending the colon.B arium enemasc an be used for the diagnosis of inflammatoryb owel diseases, diverticulum, and intestinal structuralc hanges. Double-contrast barium meal (DCBM) is another form of radiocontrast for imaging of the colon and rectum, and it involves the use of two contrast agentst ov isualize the intestinal structure more easily.…”
Section: Double-contrast Methodsmentioning
confidence: 99%
“…Double‐contrast barium enema is often applied to CT imaging of the colon, and the gas administered orally can help to distend the bowel, which enhances the contrast and allows for better differentiation of abnormal morphology from normal tissues . Barium is used to outline the colon and rectum, and air is pumped into the rectum and colon to enhance the imaging further by distending the colon.…”
Section: Contrast Agents For Ctmentioning
confidence: 96%